Increased interlayer bonding strength of short carbon fiber composite fabricated by material extrusion via warm isostatic pressing (WIP) process - Seong Jun Park; Do Hyun Kim; Ho Gi Ju; Seong Je Park; Sukjoon Hong; Yong son; Il Hyuk Ahn (Journal of Materials Research and Technology, 2023)
Recently, short carbon fiber-reinforced plastic (SFRP) has been selected as a filament material to improve the strength of components fabricated by material extrusion (ME). However, despite the improved material properties, the weak interlayer bonding and voids present in the microstructure constitute defects that cause anisotropy in the SFRP composite and deteriorate its mechanical properties such as the tensile, compressive, and flexural strengths. In this study, warm isostatic pressing (WIP) was investigated as a means to increase the interlayer bonding force and reduce the voids. To increase the efficiency of WIP, vacuum packing was investigated as a means to promote interfacial strength and diffusion between the layers. The WIP process improved the tensile, compressive, and flexural properties, and the anisotropy decreased with increasing interlayer bonding force. In addition, the thermal properties improved with an increase in the degree of crystallinity, and the voids in the microstructure were effectively reduced. These results indicate that WIP is a promising post-processing treatment for ME-fabricated SFRP parts.